EMOTIONAL REGULATION AND MENTAL HEALTH AMONG AGEING POPULATIONS: PATHWAYS TO HEALTHY AGEING - Nisha Raj; U.V Kiran; Gautam, Shikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of the present study is to assess Role of Emotional Regulation and for Mental Health among ageing individuals. For the present study a self-made socio-demographic questionnaire including variables such as age, gender, educational qualification, working status, marital status, area of living was included and to get insights about their present health condition we included variables such as living situation (i.e. whether they are living alone or with their family/caregiver), presence or absence of any disease and the level of independence for doing day to day activities; to assess the emotion regulation we used ERQ(Emotion regulation questionnaire) by Gross and John (2003), and General Health Questionnaire (GHQ-12) by Goldberg and Williamson, 1988. We selected 120 elderly individuals residing in two different localities of the Lucknow city, including equal proportions of both the genders i.e. 60 males and 60 females. After conducting this study, there is signifying negative correlation between ERQ and GHQ was found correlation coefficient (r = 0.112), therefore, we can say that healthy emotional regulation coping strategy affects mental health of elderly.